(untitled) (Revista Científica Integrada, 2025)
Objective: To map the literature on the possible impacts of spirituality on the mental health of university students during the COVID-19 pandemic. Methods: Scoping review according to the Joanna Briggs Institute methodology. An initial limited search was conducted in June 2024 in MEDLINE/PubMed and Scopus to identify articles on the topic. The words in the titles and abstracts of relevant articles and the terms used to describe the articles were used to create a complete search strategy for MEDLINE, EMBASE, Scopus and Web of Science. Results: 14 articles were selected for review, and their contents were summarized in three axes: methodological design; samples and countries in relation to the pandemic context; research objectives and findings in relation to the concepts of spirituality and mental health. Conclusion: Spirituality acts as a protective factor against maladaptive reactions to loss, especially during a pandemic. It functions as a positive coping strategy and reduces avoidance behaviors, reduces anxiety and depression, and contributes to the mental well-being of university students during times of crisis.